Combining the square of a sum formulas

Meet the square of binomials formulas:

Product of the sum of two terms and their difference

(X+Y)(XY)=X2Y2(X + Y)\cdot(X - Y) = X^2 - Y^2

Click here to read more about Multiplication of the sum of two elements by the difference between them!

The difference of squares formula

(XY)2=X22XY+Y2(X - Y)^2=X^2 - 2XY + Y^2

Click here to read more about the formula for the difference of squares

The Square of a Sum Formula

(X+Y)2=X2+2XY+Y2(X + Y)^2=X^2+ 2XY + Y^2

Click here to read more about the formula for the Sum of Squares

Formulas relating to two expressions cubed

(a+b)3=a3+3a2b+3ab2+b3(a+b)^3=a^3+3a^2 b+3ab^2+b^3

(ab)3=a33a2b+3ab2b3(a-b)^3=a^3-3a^2 b+3ab^2-b^3

Click here to read more about Formulas for Cubic Expressions

Example

Practice an exercise that combines all the shortened multiplication formulas together:
x2+(5+x)(5x)+x26x+9(63+362x+36x2+x3)=(2+x)2+(6+x)3x^2+(5+x)(5-x)+x^2-6x+9-(6^3+3\cdot 6^2\cdot x+3\cdot 6\cdot x^2+x^3)=(2+x)^2+(6+x)^3

Let's start from the beginning of the exercise. Observe that the expression
(5+x)(5x)=25x2(5+x)(5-x)=25-x^2
matches the product of the sum of th two terms and their difference
(X+Y)(XY)=X2Y2(X + Y)\cdot(X - Y) = X^2 - Y^2
Let's proceed to the expression x26x+9x^2-6x+9
We notice that it matches the difference of squares formula
(XY)2=X22XY+Y2(X - Y)^2=X^2 - 2XY + Y^2
However let's avoid touching it at this stage.
Let's continue to 63+362x+36x2+x36^3+3\cdot 6^2\cdot x+3\cdot 6\cdot x^2+x^3
and we can see that it perfectly matches the formula for two terms cubed
(a+b)3=a3+3a2b+3ab2+b3(a+b)^3=a^3+3a^2 b+3ab^2+b^3
which means
63+362x+36x2+x3=(6+x)36^3+3\cdot 6^2\cdot x+3\cdot 6\cdot x^2+x^3=(6+x)^3

Let's continue to the second side and observe that the expression (2+x)2(2+x)^2 matches the formula for sum of squares
(X+Y)2=X2+2XY+Y2(X + Y)^2=X^2+ 2XY + Y^2
Therefore
(2+x)2=4+4x+x2(2+x)^2=4+4x+x^2

Now let's insert the data:
x2+25x2+x26x+9(6+x)3=4+4x+x2+(6+x)3x^2+25-x^2+x^2-6x+9-(6+x)^3=4+4x+x^2+(6+x)^3
Let's reduce the terms and solve as follows:
6x+34=4x+4-6x+34=4x+4
Move the terms to opposite sides:
8x=308x=30
x=3.75x=3.75

Suggested Topics to Practice in Advance

  1. The formula for the Sum of Squares
  2. The formula for the difference of squares
  3. Abbreviated Multiplication Formulas
  4. Multiplication of the sum of two elements by the difference between them

Practice Combining Short Multiplication Formulas

Examples with solutions for Combining Short Multiplication Formulas

Exercise #1

Solve the following equation:

(x4)2+3x2=16x+12 (x-4)^2+3x^2=-16x+12

Video Solution

Answer

x=1 x=-1

Exercise #2

Solve the following equation:

(x+2)2=(2x+3)2 (x+2)^2=(2x+3)^2

Video Solution

Answer

x1=1,x2=53 x_1=-1,x_2=-\frac{5}{3}

Exercise #3

Find X

7x+1+(2x+3)2=(4x+2)2 7x+1+(2x+3)^2=(4x+2)^2

Video Solution

Answer

1±338 \frac{1\pm\sqrt{33}}{8}

Exercise #4

Solve the following equation:

(x+3)2=2x+5 (x+3)^2=2x+5

Video Solution

Answer

x=2 x=-2

Exercise #5

Solve the equation

2x22x=(x+1)2 2x^2-2x=(x+1)^2

Video Solution

Answer

Answers a + b